Near-infrared long lifetime upconversion nanoparticles for ultrasensitive microRNA detection via time-gated luminescence resonance energy transfer - Suyeon Kim; Yeonkyung Park; Jiwoo Han; Hansol Kim; Hyowon Jang; Sohyung Kim; Dongkyu Kang; Min-Young Lee; Byeong-Ho Jeong; Yuree Byun; Eun-Kyung Lim; Juyeon Jung; et al. (Nature Communications)
Abstract Upconversion nanoparticle (UCNP)-based luminescence resonance energy transfer (LRET) biosensing offers advantages such as wash-free detection and precise biomolecule quantification. However, its sensitivity remains limited due to continuous energy transfer in co-doped UCNPs during LRET. Here we present a time-gated LRET strategy using near-infrared (NIR) long-lived luminescent UCNP donors (L-TG-LRET), achieving an 8-fold increase in luminescence lifetime without compromising emission intensity. This prolonged energy migration and transfer pathway significantly enhances sensitivity by preventing rapid Tm3+ reactivation during LRET to IRDye800 acceptors. Applying this approach to microRNA (miRNA) detection, we achieve a 17.9-fold higher sensitivity than conventional steady-state methods. Furthermore, the L-TG-LRET successfully quantifies miRNA expression in cancer cells, plasma, and exosomes, enabling the differentiation of cancer patients from healthy donors. Notably, this approach outperforms polymerase chain reaction in detecting low-abundance exosomal miRNAs. These results highlight the potential of L-TG-LRET system as a valuable tool for sensitive biomolecular detection in clinical diagnostics.